IMPACT OF DIGITAL TRANSFORMATION ON CUSTOMER SATISFACTION IN THE BANKING SECTOR: A DESCRIPTIVE STUDY (International Journal of Food and Nutritional Sciences, 2023)
The emergence of digital transformation has brought a lot of changes in the banking sector, as the industry has been redefined in terms of service delivery to the customers. The descriptive study will highlight how digital transformation